FAKTOR-FAKTOR PENYEBAB RENDAHNYA MINAT SISWA TERHADAP EKSTRAKURIKULER OLAHRAGA DI SMK NEGERI 1 SLAHUNG PONOROGO - PRASETYO, YUDI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Extracurricular is an education activity which is done out of the usual school hours and counseling service which aims to help the students’ development based on their needs, potential, talents. Meanwhile, there is a fact that the extracurricular activity is impeded by the low interest of the students to participate. Based on that fact, the amount of participants in basketball,  volleyball and football extracurricular in Vocational High School 1 Slahung Ponorogo is on the wane. This shows that the students’ interest in extracurricular activities in Vocational High School 1 Slahung Ponorogo is low. This research aimed to investigate what factors which cause the low interest of the students in extracurricular physical activities in Vocational High School 1 Slahung Ponorogo and also to investigate the dominant factors which cause it. The research design used was descriptive qualitative and then analyzed by using regression analysis. The result of this research showed that the factors which cause the low interest of the students in extracurricular physical activities in Vocational High School 1 Slahung Ponorogo were the aspect of feeling which has the coefficient of 0,345, 0,134 for the physical condition, 0,119 for the students’ interest to choose the other activities, 0,145 for family, 0,149 for the instructor of extracurricular activities, 0,189 for the facilities and infrastructures, 0,110 for friends, 0,165 for geographical condition, and also transportations with the coefficient of  0,158. The dominant factors which caused the low interest of the students in extracurricular physical activities in Vocational High School 1 Slahung Ponorogo generally were feeling aspect  which has the coefficient of 0,345, the facilities and infrastructures aspect with the coefficient of 0,189, and also geographical condition with the coefficient of 0,165. In conclusion, the factors which cause the low interest of the students in extracurricular physical activities in Vocational High School 1 Slahung Ponorogo consist of feeling aspect, physical condition, the students’ interest to choose other activities, parents, the teacher/instructor of extracurricular activities, facilities and infrastructure aspect, friends, geographical condition, and transportations. Whereas the dominant factors generally are feeling aspect, facilities and infrastructure aspect, and geographical condition. Keywords : interest, students, sports extracurricular activities